Design Of A Picture Story Book DKV Picture Story Book - Suprianingsih Suprianingsih; Desipriani Desipriani; Juli Atika (International Journal of Graphic Design, 2023)
This illustrated story book takes up the theme of the world of visual communication design with the title "DKV Dunia Color Adventure" which tells about a child named Bella who really likes the world of visual communication design, in this book it is told about Bella who is confident of delving into the world of visual communication design after meeting several adults who have dabbled in the world of visual communication design. One by one they explain everything that is available in the world of visual communication design according to their areas of expertise in the world of design. This is what attracts more and more people to know more about the world of visual communication design.